The church and diaconia as local partners in the social space: Challenges and opportunities - Eurich, Johannes (HTS teologiese studies, 2020)
Demographic change, change in family structures, growing ethnic plurality resulting from migration, social inequality and so on require new ways of addressing spiritual and social needs in many Western European countries. In view of these current social changes, increasingly more effort is being put into strengthening cooperation between church congregations and diaconal institutions at the local level. This article will focus on the reciprocal relationship between the church and its immediate local context by focusing on one of the church’s ministries – diaconia – as a service of God’s people to the world. Although diaconia is part of the church, it has developed in organisations separate from the church and thus as a parallel structure to the institutionalised church structure in many countries. The current changes offer opportunities for the church and diaconia to join forces and to overcome cooperational difficulties at the local level. The objective of this article is to draw attention to the potential of the social space for collaboration, to analyse hindrances to collaborative efforts on a practical level and to point out what steps the church and diaconia may take to further local collaboration.Contribution: The contribution of this article is to analyse the social space with regard to the collaboration between local churches and diaconal organisations, and thereby to point out its potential for their further development in line with the journal’s focus on original ideas in practical theology.